Figure of Speech in the Poetry Mitos Vreemde Oosterlingen dan Inlander and the Poetry Habib by Zeffry Alkatiri - S. Samsuddin (Universitas Sembilanbelas November Kolaka, 2017)
Figure of speech (Majas) is the means by which the poet writes ideas, thoughts, and feelings to convey. Through the use of the Majas, the messages that are rough, instantaneous become more polished, more polite, more accepted by the readers. Majas can be found in all poem including poems written by Zeffry Alkatiri in general, especially poetry. The use of Majas can be traced to the poems of the “Mitos Vreemde Oosterlingen dan Inlander” and “Habib”. Both of these poems empower the Majas of Comparison in the form of analogy with a little metaphor to get around the message the poet is trying to convey.